O perigo de uma historia única: a “invenção” de Codó - Ma como terra da macumba (1950 a 1990) São Luís 2015. - RIBEIRO, Jéssica Cristina Aguiar (2015)
This work left the problem of reflecting as speeches were able to showcase representation of the city of Codo-Ma as the voodoo land. We seek to understand how the knowledge-power of the media (printed newspapers and documentaries) potentiated images of the city and its townspeople, and the objective is to identify which stigmas were created on Bita the Baron in order to understand what relationship it has with the spread of images and discourses on Codó as a place of "great macumbeiros". The guiding research methods are pedigree (Nietzche-Foucault) and evidentiary (Morelli-Ginzburg) in order to seek not the source, the "real beginning" of Codo-Ma invention as land voodoo, but the constituent parts crystallized representation. KEYWORDS. City.